REPRESENTATION, IMAGINARY AND CULTURAL RECOGNITION: A CRITICAL ANALYSIS OF LAW No. 30153 DECLARING THE PROTECTION AND PROMOTION OF THE "CULTURE JAQARU" - Ramírez Trebejo, Andrés (2015)
In late 2013, the Congress of the Republic of Peru unanimously approved the Law No. 30153, law declares of national interest and public need protection, research and promotion of culture and language Jaqaru, and archaeological monuments located in the district of Tupe, Yauyos province, Lima department. This legislative initiative was aimed to revalue the cultural aspects of a town in the Peruvian Andes, it was not without critical and disputes between those trying to represent those who were represented; that is, between those who developed and promoted the law and the authorities and residents of Tupe. Thus, in this article an analysis of the law is provided, addressing their history, the actors were at play, content, and above all, the tensions originated by the representation and recognition of tupina society.